2010
DOI: 10.1007/s11255-010-9746-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intradialytic hypotension using impedance cardiography

Abstract: Hemodynamic changes in dialysis patients with hypotensive episodes included decreased cardiac output or decreased peripheral resistance. A lower end-diastolic filling ratio may be regarded as a marker for reduced preload in these patients. Non-invasive impedance cardiography may be used to evaluate risk factors for hypotension in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These mechanisms are predominantly regulated by the sympathetic nervous system and the renin-angiotensin system. Although dialysis patients generally have an overactive sympathetic nervous system and renin-angiotensin system [8,9,10,11,12], the increase in peripheral resistance is insufficient to prevent intradialytic hypotension in many patients [13,14]. As a consequence, the role of the vasoconstrictor arginine vasopressin (AVP) for maintaining blood pressure may become increasingly important [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms are predominantly regulated by the sympathetic nervous system and the renin-angiotensin system. Although dialysis patients generally have an overactive sympathetic nervous system and renin-angiotensin system [8,9,10,11,12], the increase in peripheral resistance is insufficient to prevent intradialytic hypotension in many patients [13,14]. As a consequence, the role of the vasoconstrictor arginine vasopressin (AVP) for maintaining blood pressure may become increasingly important [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms responsible for decreased BP during HD are rapid excessive ultrafiltration , a rapid reduction in plasma osmolality , an incorrectly low prescribed target weight , autonomic neuropathy , diminished cardiac reserve , excessive antihypertensive medications , and the composition and temperature of the dialysate fluid . Bayya et al demonstrated that a lower calculated end‐diastolic filling ratio, which is defined as the diastolic amplitude of the impedance cardiogram divided by the systolic amplitude, was an independent predictor for decreased BP during HD . The low end‐diastolic filling ratio may be regarded as a marker for a reduced preload in these patients.…”
Section: Discussionmentioning
confidence: 99%